Avaliação por pig de perfilagem de danos superfciais nos materiais das paredes de dutos de petróleo - Sabino, João Marcos (2009)
The modern technology of materials and structural integrity of pipelines requests the use of inspection tools named inspection pigs to detect, localize and measure the length, width and depth dimensions of the thickness losses of walls of buried and underwater pipelines in service. These tools run them internally, performing and recording measurements, with performance that varies according to the pig s technology. It has been developed recently an instrumented pig technology, called feller pig. This work aims to indicate factors that influence the feller pig technology performance in the detection and in the accuracy of measurement of the length, width and depth dimensions of the thickness losses on the internal surface of an oil pipeline wall under normal conditions of oil pipe inspection with pig. In this work, is made a collection of factors and an analyses of the technology based on the available literature, as well as an experiment to observe the technology and the factors operating. In the experiment, a feeler pig is used in a pipeline built in carbon steel and in operation that flows petroleum, in witch are observed areas with internal thickness losses occurred naturally. Some of these areas and their dimensions taken by automated ultra-sound scanner are compared with the ones indicated by the feller pig. Based on the data collection, on the analysis and on the experiment, the influence of factors object of this research is discussed. It is concluded that, among these, there are factors related to pipe fabrication tolerances, to wear of pig components, to internal adhesive wear of pipeline, to other pipeline damages and to technology characteristics. Finally, actions are suggested to know better, improve and define the applicability of this technology